Apresentação e Organização - dos Santos, Rodrigo Pereira; Moura, Raimundo Santos (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2018)
Apresentação e Organização do VII Brazilian Workshop on Social Network Analysis and Mining .